2016
DOI: 10.1186/s13075-016-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation mechanism of RANKL+ effector memory B cells: relevance to the pathogenesis of rheumatoid arthritis

Abstract: BackgroundThe efficacy of B cell-depleting therapies for rheumatoid arthritis underscores antibody-independent functions of effector B cells such as cognate T–B interactions and production of pro-inflammatory cytokines. Receptor activator of nuclear factor κB ligand (RANKL) is a key cytokine involved in bone destruction and is highly expressed in synovial fluid B cells in patients with rheumatoid arthritis. In this study we sought to clarify the generation mechanism of RANKL+ effector B cells and their impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 38 publications
4
30
0
1
Order By: Relevance
“…Although the reason for this difference between T and B cells is unclear, RANKL expressed by lymphocytes was found to be involved in supporting osteoclastogenesis in vitro . In other studies of B cells and the skeletal system as well as its related diseases, researchers found that B cells were prone to aggregate at the interface between bone marrow and inflammation hard tissues, in which osteoclastogenesis was active and cortical bone had been damaged . Mice with B cells lacking the RANKL gene showed a defensive effect of estrogen deficiency‐related osteopenia, indicating that B cells promote osteoclastogenesis by producing RANKL …”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this difference between T and B cells is unclear, RANKL expressed by lymphocytes was found to be involved in supporting osteoclastogenesis in vitro . In other studies of B cells and the skeletal system as well as its related diseases, researchers found that B cells were prone to aggregate at the interface between bone marrow and inflammation hard tissues, in which osteoclastogenesis was active and cortical bone had been damaged . Mice with B cells lacking the RANKL gene showed a defensive effect of estrogen deficiency‐related osteopenia, indicating that B cells promote osteoclastogenesis by producing RANKL …”
Section: Discussionmentioning
confidence: 99%
“…Activated B lymphocytes have been suggested as a primary source of RANKL in inflamed liver . Recently, it was reported that B cells spontaneously produce RANKL and correspondingly promote osteoclastogenesis and contribute to bone erosion in patients with inflammatory arthritis . It has also been reported that RANKL‐producing regulatory T cells promote mammary cancer metastasis through activation of an inhibitor of nuclear factor kappa B (NF‐κB) kinase alpha (IκBα), suggesting that targeting RANKL–RANK can potentially modulate cancer metastasis .…”
mentioning
confidence: 99%
“…Moreover, anti-B cells therapy leads to a reduction of bone resorption in RA and seems to be beneficial in improving periodontitis [ 14 ]. In RA, activation through BCR and CD40 induces switched memory B cells to express RANKL and leads to the activation of osteoclastogenesis [ 47 ]. A similar mechanism could be suspected in periodontitis and could explain the general increase in the observed RANKL expression on B cells in our study.…”
Section: Discussionmentioning
confidence: 99%